Liberalization in telecommunications - Andreas Knorr (Hamburg Institute of International Economics (HWWA), 2002)
During the past two decades, international trade in telecommunication services has significantly intensified. What is more, an increasing number of telecommunications operators have begun to expand their activities beyond national borders through FDIs, joint ventures, and cooperation agreements. In this paper it is argued, however, that in spite of the rather successful efforts of late to liberalize the telecommunications sector (networks and services) at the regional (EU) and the global (WTO) level, much remains to be done to create and preserve a truly open and competitive worldwide telecommunications market. – – In den vergangenen beiden Jahrzehnten hat sich der internationale Handel mit Telekommunikationsdienstleistungen wesentlich intensiviert. Parallel dazu begannen immer mehr Telefongesellschaften, sich durch Direktinvestitionen, Joint ventures und Kooperationen auch auf ausländischen Märkten zu engagieren. Wie in dem vorliegenden Papier gezeigt wird, kann allen bisherigen Liberalisierungserfolgen der jüngeren Vergangenheit auf regionaler (EU) und globaler Ebene (WTO) zum Trotz von einem offenen globalen Markt für Telekommunikationsdienste und damit auch von einem freien, unverfälschten Wettbewerb zwischen alternativen Netz- und Diensteanbietern noch immer nicht die Rede sein.
Keywords: L96; F13; F02; 330; International Economic Order; Trade Negotiations; Services Liberalisation; Telecommunications Services; Telekommunikation; Internationaler Dienstleistungsverkehr; Außenhandelsliberalisierung; Telekommunikationspolitik; Deregulierung; Welt